Робастная система управления пьезодвигателем - Кузнецов, Борис Иванович; Никитина, Татьяна Борисовна; Кузнецова, Людмила Георгиевна; Коломиец, Валерий Витальевич; Курцева, Лилия Борисовна; Еремина, Наталья Сергеевна (НТУ "ХПИ", 2010)
This article deals with robust control system for piezo motor as two mass electromechanically system. The example of dynamic characteristics for such system is given.
Robust control system of piezo motor
Keywords: система электромеханическая; регулятор; усилие; скорость; деформация